Mass surveillance in the age of COVID-19 - Ram, Natalie (J Law Biosci, 2020)
Epidemiological surveillance programs such as digital contact tracing have been touted as a silver bullet that will free the American public from the strictures of social distancing, enabling a return to school, work, and socializing. This Article assesses whether and under what circumstances the United States ought to embrace such programs. Part I analyzes the constitutionality of programs like digital contact tracing, arguing that the Fourth Amendment’s protection against unreasonable searches and seizures may well regulate the use of location data for epidemiological purposes, but that the legislative and executive branches have significant latitude to develop these programs within the broad constraints of the ``special needs'' doctrine elaborated by the courts in parallel circumstances. Part II cautions that the absence of a firm warrant requirement for digital contact tracing should not serve as a green light for unregulated and mass digital location tracking. In light of substantial risks to privacy, policy makers must ask hard questions about efficacy and the comparative advantages of location tracking versus more traditional means of controlling epidemic contagions, take seriously threats to privacy, tailor programs parsimoniously, establish clear metrics for determining success, and set clear plans for decommissioning surveillance programs.